LIMITS AND TREATMENT INDICATIONS FOR PROSTHETIC TREATMENT IN ELDERLY EDENTULOUS PATIENTS - Dana Budală; Silvia Mihaela Silvas; Dan Nicolae Bosânceanu; Roxana Vasluianu (Romanian Dental Association for Education, 2013)
Reconstructing the edentulous arches is a very serious issue for the elderly patient because of the difficulties that may occur during the process of making the dentures, reestablishig the vertical dimension, recovering the facial aspect modified with age, cleaning and maintaining the dentures, all problemes due to the third age. The organism is also changed and not so flexible, the habits, the changes in the environement ask for changes that the elderly is no longer available to do them. Adjusting to new conditions is difficult if not impossible sometimes and this is a real impediment for patient, which had also lower the ability to recognize shape and dimension of objects. The study was conducted on a group of 46 patients, 19 men and 27 women, with complete or subtotal edentation, denture weares or not, with ages over 60 years old, average age being 70.3.General exam, anamnesis, interdisciplinarity allowed establishing a very precise diagnosis of general state of health (heart diseases, metabolic diseases, lungs or kidney diseases, osseous disease, etc). Statistics proves that from 46 examined patients, 24 of them had a stressed geroindex, 17 of them were near the normal limits and 5 were younger than their biological age. The oral exam showed facial changes caused by age and edentation: lower inferior floor, facial asymmetries, stressed wrinkles and ditches, reduced lips.